Utility of a Quantitative Approach Using Diffusion Tensor Imaging for Prognostication Regarding Motor and Functional Outcomes in Patients With Surgically Resected Deep Intracranial Cavernous Malformations. Issue 5 (30th July 2019) - Abhinav, Kumar; Nielsen, Troels H; Singh, Rhea; Weng, Yingjie; Han, Summer S; Iv, Michael; Steinberg, Gary K
Abstract: BACKGROUND: Resection of deep intracranial cavernous malformations (CMs) is associated with a higher risk of neurological deterioration and uncertainty regarding clinical outcomes. OBJECTIVE: To examine diffusion tractography imaging (DTI) data evaluating the corticospinal tract (CST) in relation to motor and functional outcomes in patients with surgically resected deep CMs. METHODS: Perilesional CST was characterized as disrupted, displaced, or normal. Mean fractional anisotropy (FA) values were obtained for whole ipsilateral CST and in 3 regions: subcortical (proximal), perilesional, and distally. Mean FA values in anatomically equivalent regions in the contralateral CST were obtained. Clinical and radiological data were collected independently. Multivariable regression analysis was used for statistical analysis. RESULTS: A total of 18 patients [brainstem (15) and thalamus/basal ganglia (3); median follow-up: 270 d] were identified over 2 yr. The CST was identified preoperatively as disrupted (6), displaced (8), and normal (4). Five of 6 patients with disruption had weakness. Higher preoperative mean FA values for distal ipsilateral CST segment were associated with better preoperative lower ( P < .001), upper limb ( P = .004), postoperative lower ( P = .005), and upper limb ( P < .001) motor examination. Preoperative mean FA values for distal ipsilateral CST segment ( P = .001) and contralateral perilesional CST segment ( P < .001) were negatively associated with postoperative modified Rankin scale scores. CONCLUSION: Lower preoperative mean FA values for overall and defined CST segments corresponded to worse patient pre- and postoperative motor examination and/or functional status. FA value for the distal ipsilateral CST segment has prognostic potential with respect to clinical outcomes.